ANALISIS UNSUR INTRINSIK NOVEL HIJRAH ITU CINTA KARYA ABAY ADHITYA - Qholisna Munanar (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
Literature is a language that is expressed both in writing and orally by the author based on experience and even feelings. A moral message is a mandate or advive conveyed by the author in a story he has written in order to provide an opinion related to moral teachings. Researchers are very interested in analyzing novels that have quite a lot of moral values. This research focuses on the analysis of the intrinsic elements of the novel which aims to describe the intrinsic elements in the novel “Hijrah itu Cinta” by Abay Adhitya. The reserch method in analyzing the novel uses a qualitative descriptive method. The result of the study, explained that the novel Hijrah itu Cinta raises the theme of life, there is a moral message contained in the novel. The conclusion in this study can be concluded that the author tells the sweet and bitter journey of hijrah, the moral message conveyed by the author in the novel is a dark past raises awareness to change oneself for the better. Through this research, it is hoped that lessons can be drawn for changes for the better for readers of the novel Hijrah itu Cinta.